1997
DOI: 10.2307/1592148
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Characterization of a Turkey Coronavirus Identified in Poult Enteritis- and Mortality Syndrome-Affected Turkeys

Abstract: A turkey coronavirus (TCV [NC95]) was characterized by antigenic comparison with other avian and mammalian coronaviruses using immunofluorescence (FA) and immunoperoxidase (IP) procedures. Based on FA and IP procedures, TCV (NC95) was determined to be antigenically indistinguishable from turkey enteric (bluecomb) coronavirus (TECV). In addition, TCV (NC95) and TECV were found to be closely related to infectious bronchitis virus (IBV); a one-way antigenic relationship was demonstrated. Polyclonal antibodies spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 10 publications
3
56
0
4
Order By: Relevance
“…Normally, immunohistochemical reaction protocols involve using two antibodies, the primary antibody and the second, which is a conjugated antibody directed against immunoglobulin of the target animal species. Research in the mid-1990s showed that coronavirus from turkeys were genetically (Breslin et al, 1999a,b) and antigenically (Guy et al ., 1997;Breslin et al, 2000;Guy, 2003) closely related to IBV, as confirmed elsewhere (Cavanagh et al ., 2001). It is true that using polyclonal antibodies increases sensitivity and is less laborious compared with monoclonal antibody protocols (Cardoso et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, immunohistochemical reaction protocols involve using two antibodies, the primary antibody and the second, which is a conjugated antibody directed against immunoglobulin of the target animal species. Research in the mid-1990s showed that coronavirus from turkeys were genetically (Breslin et al, 1999a,b) and antigenically (Guy et al ., 1997;Breslin et al, 2000;Guy, 2003) closely related to IBV, as confirmed elsewhere (Cavanagh et al ., 2001). It is true that using polyclonal antibodies increases sensitivity and is less laborious compared with monoclonal antibody protocols (Cardoso et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Some 25 years ago it was suggested that TCoV was closely related to BCoV of Group 2 (Dea et al ., 1990). We now know that this is not the case and that TCoV is unequivocally closely related to IBV, both in terms of gene and protein sequences (Breslin et al ., 1999a,b;Cavanagh et al ., 2001), and also antigenically (Guy et al ., 1997;Breslin et al, 2000;Loa et al ., 2000).…”
Section: Coronaviruses: the Three Groupsmentioning
confidence: 99%
“…Research at the University of North Carolina in the mid1990s showed that coronaviruses from turkeys were genetically (Breslin et al ., 1999a,b) and antigenically (Guy et al ., 1997(Guy et al ., , 2002Breslin et al ., 2000) closely related to IBV, confirmed elsewhere Ismail et al ., 2001a) reviewed by Guy (2000). Indeed, antibodies binding to IBV antigens had been detected in turkey sera as early as 1987 by Weissman et al .…”
Section: Relationship Between Ibv and Tcovmentioning
confidence: 99%
“…Infectious bronchitis virus (IBV) and turkey coronavirus (TCoV) belong to group III of Coronaviridae. 3,7,15 Turkey coronavirus causes an acute, highly infec- tious disease affecting turkeys of all ages. The disease is known by various names.…”
mentioning
confidence: 99%
“…Recent studies have strongly indicated a close antigenic as well as genetic relationship between these 2 important viruses. 1,3,7,15 The complete nucleotide sequence of the N gene and a portion of the M gene were analyzed, and their projected amino acid sequences were found to be very similar (more than 90%) to those of IBV M and N proteins. 1,3,15 The amplification of the IBV genome can be explained on the basis of the abovementioned observation.…”
mentioning
confidence: 99%